Micrometeorological characterization of protected environments for plant production - da Silva, Abimael Gomes [UNESP]; Costa, Edilson; Zoz, Tiago; da Silva Binotti, Flávio Ferreira (Revista de Agricultura Neotropical, 2021)
This study evaluates the influence of the four seasons and twelve months of the year on the micrometeorological variables of global solar radiation, air temperature, and relative air humidity in different protected environments for plant production. The protected environment types and the characteristics of the shade screen modify the indoor air temperature. This environment provides greater relative humidity. The global solar radiation percentages in the environments were: full sun (100%); black screen with 30% shading (47.3%); greenhouse with LDPE + 22-30% shading screen under the film (38.1%); aluminized screen with 35% shading (36.9%) and greenhouse with LDPE + 42-50% shading screen under the film (26.9%). The micrometeorological conditions of environments such as air temperature, relative air humidity, and global solar radiation in the seasons of year are similar to the behavior verified in the monthly test. Air temperatures and global solar radiation formed two distinct groups, with the spring and summer seasons being considered one group and autumn and winter another group. The summer and autumn periods showed the highest relative humidity compared to the winter and spring periods, with a low percentage of air humidity. Seasons in the study region are not as well defined as those in the northern hemisphere.
Caracterização micrometeorológica de ambientes protegidos para a produção vegetal
Keywords: Relative humidity; Seasons; Solar radiation; Temperature